Does Employment Effeciveness Indicator Yield a Performance Paradox? - Piwowarski, Radosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
In the report about effectiveness of selected Active Labor Market Programs (ALMP) published in 2015 by the Supreme Audit Office (NIK) one can find conclusions which may indicate the occurrence possibility of the performance paradox. This applies primarily to the employment effectiveness indicator (WEZ), which is widely used by the district labor offices in Poland. The aim of the article is to characterize the phenomenon of the performance paradox and assess the possibility of its occurrence in the case of WEZ. To complete the goal data published by the Ministry of Labour and the Central Statistical Office relating to ALMP for the years 2009–2014 is analyzed. Moreover, correlation analysis between WEZ and the rates of outflow from unemployment due to employment and employment after participation in ALMP is conducted. The analysis show that the presented by Ministry of Labour reports about effectiveness of district labor offices are more optimistic than the actual. This is a phenomenon characteristic for the performance paradox, which WEZ seems to yield.